PENGENALAN KOMODITAS BUAH-BUAHAN DENGAN METODE PEMBELAJARAN INTERAKSI SOSIAL DI POS PAUD PERMATA HATI SURAKARTA: INTRODUCTION OF FRUIT COMMODITIES USING SOCIAL INTERACTION LEARNING METHODS AT PERMATA HATI PRESCHOOL SURAKARTA - Rahmawati Setiyani; Esti Dwi Rahmawati (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Fruits are one of the horticultural commodities that play an important role for the health of the body. Fulfillment of balanced nutrition needs to be done because good nutrition will go hand in hand with good health. Nutrition Guide for Balanced Diet is the principle of consuming daily foods that contain nutrients in the type and amount according to the needs of each person according to the age group. Early childhood is a child in the age range of 0 to 6 years old who has a golden age where children develop rapidly. Early childhood requires quality and creative social interactions so that children are motivated. The purpose of this Community Service activity is to provide education on the introduction of local Indonesian fruit commodities with social interaction learning methods to students at Permata Hati Preschool Surakarta City. The method used is social interaction learning so that students have the will to consume fruits as an effort to fulfill balanced nutrition that supports growth. The activities that have been carried out have resulted in students from the Permata Hati Preschool Surakarta City knowing local Indonesian fruits and having a willingness to eat fruit to support growth.